1909 Idaho Sess. Laws 6, No. 62, § 1 - (:unkn) unknown (General Publisher, 1909)
Prohibited the carrying a concealed dirk, Bowie knife, dagger, slungshot, pistol, revolver, gun, or any other deadly or dangerous weapon in any public setting.
--
Keywords: CARRY - CONCEALED